Analysis of the effect of platelet-derived growth factor combined with T cells in the diagnosis of hepatocellular carcinoma and poor prognosis - Wu, Fei; Chen, Guo; Wang, Zuxin; Niu, Youquan; Zhang, Wenqing; Jiang, Hua (Journal of Medical Biochemistry, 2025)
Objective: The aim of this study is to investigate the diagnostic and prognostic value of combined detection of serum platelet-derived growth factor (PDGF) and Treg/Th17 in hepatocellular carcinoma (HCC).Methods: We included 204 HCC patients managed with drug eluting beads-transcatheter arterial chemoembolization (D-TACE) and 100 healthy controls. Serum PDGF concentrations were measured via enzyme-linked immunosorbent assay (ELISA), while flow cytometry quantified Treg and Th17 cell proportions. The predictive performance of PDGF, Th17/Treg, and their combination for HCC diagnosis, therapeutic response, and 1-year overall survival (OS) was evaluated using receiver operating characteristic (ROC) analysis, Kaplan-Meier survival curves, and multivariate regression models. Results: HCC cases exhibited notable elevations in serum PDGF concentrations and Th17/Treg than healthy controls, with tumor tissue PDGF expression significantly correlating with serum levels (P
Keywords: PDGF; Th17/Treg; liver cancer; D-TACE; combined detection; diagnosis